The PENGARUH PEMBIAYAAN INVESTASI DAN BOPO TERHADAP ROA PADA LEMBAGA PEMBIAYAAN DI INDONESIA TAHUN 2021 - R. Deden Adhianto (EKBIS (Ekonomi & Bisnis), 2022)
Financing Institutions have an important role in supporting business and economic activities. In addition, it can encourage the creation of prosperity. Therefore, this study was conducted to determine the effect of Investment Financing and Operational Costs and Operating Income (BOPO) on the profitability of the Financing Institution. Profitability chosen is Return On Assets which is a parameter that is in accordance with the prevalence of profitability measurement and the rules of the Financial Services Authority for Financing Institutions. The sample data taken is purposive sampling data in 2021 which was taken from the OJK website. In this descriptive quantitative study, multiple regression analysis was applied to test the effect (F-Test and T-Test), by testing the classical assumptions before, in order to ensure the reliability of the data. The data processing software used is SPSS version 23. From the results of data processing, it can be concluded that: a) Together, the Investment Financing Variable and the BOPO variable have a significant positive effect on the ROA variable; b) Individually, the Investment Financing Variable does not have a significant effect on the ROA variable; c) Individually, the BOPO variable has a significant effect on the ROA variable